PENGARUH BUDAYA SEKOLAH TERHADAP KUALITAS PEMBELAJARAN DI SMA NEGERI 1 KRIAN - Sefia Rahmawati; Dea Miranda; Shabrina Poppy Darmatian; Felda Ramadhanti; Alven Risqi Muchlasin; Ayu Wulandari (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This study looks at how school culture affects the standard of instruction at SMA Negeri 1 Krian in Sidoarjo Regency. The distinctive qualities and personality of a school that influence the learning environment, student motivation, and involvement are referred to as its school culture. The relationship between learning quality and school culture was examined using a quantitative methodology. School culture has a significant influence on the learning process, based on the ANOVA test which produced a significance value of 0.000 < (0.05). A student's character is shaped and their educational experience is enhanced by factors including school rules, extracurricular activities, and acknowledging student accomplishments. This study emphasizes how crucial it is to develop a positive school culture in order to provide a helpful and productive learning environment, which will ultimately raise the standard of instruction and improve student results